(untitled) (Web of Teachers: Inderscience Research, 2024)
This article provides methodological recommendations for conducting sports tourism activities, which are important for the formation and development of domestic tourism. The seasonal nature of the organization of sports tourism also raises issues that need to take into account the natural conditions of the place.